Law, anthropology, and the constitution of the social : making persons and things - Pottage, Alain; Mundy, Martha (Cambridge studies in law and society., 2004)
This book is the product of a collaboration between leading theorists in law and anthropology. It develops an innovative analysis of legal practices. Specifically, it focuses on how law produces persons and things, and develops new approaches to the question of ownership.